Damia's children - McCaffrey, Anne (Putnam, 1993)
The legacy of The Rowan lies in the psychic talent she has passed on to her children and grandchildren. In the past, the Rowan deflected alien attacks. Now, the combined abilities of her children are greater than her own and it is time for humans to confront the new attackers face to face.